Identification of new lines resistance to blackleg in an Argentinian rapeseed-breeding program - Bessone, Victoria; Acosta, Maria Gabriela; Schutt, Lorena Silvana; Gallardo, Maricel Andrea; Milisich, Hector Jose; Gieco, Lucrecia Cristina; Martín, Eugenia Alejandra (Elsevier, 2025)
Rapeseed (Brassica napus L.) is the third most important oil crop worldwide and it has a high demand for its industrial characteristics that make it suitable for human consumption and production of biofuels. The main yield losses of the crop are produce by blackleg, caused by Leptosphaeria maculans (Desmaz.) Ces. and of Not. [Anamorph Phoma lingam (Tode ex Fr.) Desmaz]. In this context, 469 inbred lines (ILs) of the INTA-EEA Paraná breeding program were phenotypic characterized for its resistance to Blackleg by artificial inoculations with a local isolation. From the initial 469 ILs, a total of 59 (13%) were identified as phenotypically resistant and were characterized by molecular makers associated to resistant genes (Rlm1, Lepr3, Rpg3Dun, and Rlm4) with the aim to identify lines carrying different resistance genes to be selected as parental lines in the development of new resistant genotypes. Moreover, the resistant ILs were characterized for its agronomics performance, including yield; percentage of oil; and content of fatty acids, over two crop seasons (2018 and 2019). A Generalized Procrustes Analysis was conducted to correlate all the traits evaluated and identify elite lines. From the 59 resistants ILs, four lines were selected based on their high performances and multiple resistant gene combinations, as started lines to develop a pyramiding gene strategy. The selection of these elite lines to combine traditional breeding and gene-pyramiding based on MAS in our breeding program is a useful strategy to develop superior rapeseed genotypes.